Konsep Maslahah al-Juwaini dalam Kitab al-Burhan fi Ushul al-Fiqh pada Penyelesaian Kasus Bayi Tabung - Sugian, Arif (STAINI Press, 2024)
This research applies qualitative research methods with a focus on literature analysis, which allows in-depth exploration of various sources that discuss the topic of IVF according to al-Juwaini's views. The data collected is then systematically analyzed to gain a deeper understanding of the subject of this research. Within the framework of al-Juwaini's concept of maslahah in Al-Burhan fi Ushul Fiqh, the use of IVF with the use of sperm and ovum from a married couple is permitted due to the urgent need in the context of marriage. However, when it involves the utilization of another woman's womb to transfer embryos, ethical and legal issues arise such as the unclear status of offspring in terms of nasab, inheritance, and the psychological impact on all parties involved. Therefore, the use of IVF by taking sperm or ovum from a donor and implanting the embryo into another woman's womb is condemned as haram in the perspective of Islamic law.